Ceftazidime/avibactam combined with colistimethate sodium successfully cures carbapenem-resistant Pseudomonas aeruginosa-induced brain abscess in a child post-craniotomy: a case report - Yuan, Minglu; Zong, Miao; Ren, Cong; Zong, Wenjing; Li, Zhongdong (Frontiers in Oncology, 2024)
The treatment of brain abscess induced by carbapenem-resistant Pseudomonas aeruginosa (CRPA) is a clinical challenge around the world. Apart from novel β-lactam/β-lactamase inhibitors and polymyxins, there are few sufficiently powerful antibiotics that are effective against CRPA-induced infections. Considering the blood-brain barrier factor, there are even fewer drugs that can be used to treat intracranial CRPA-induced infections. In this article, we reported a case of CRPA-induced brain abscess that was successfully treated with intravenous ceftazidime/avibactam and intrathecal colistimethate sodium in a child after intracranial tumor resection.